Chamantos, ponchos and Balandres in Colchagua and Rancagua (XVII-XIX centuries) - Lacoste, Pablo; Lacoste Adunka, Michelle Malén (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2018)
We study the history of ponchos, balandres and chamantos from notary and judicial sources of Colchagua and Rancagua, from the early eventeenth century to the midnineteenth century. This source provides relevant knowledge about the presence ofthese tissues in chilean society, its social and economic value, its historical cycles and its color characteristics. It demonstrates the deep rootedness of tissue culture within the mestizo society of the Central Valley of Chile, and its ties to the tradition of the indigenous world. The existence of the chamanto from the decade of 1820 in thisregion, base of the current Denomination of Origin, is demonstrated.